Consensus on Auditory Evoked Brainstem Potentials I: Results on sample of normal-hearing adults - Delgado Hernández, Jonathan; Zenker Castro, Franz; Barajas del Prat, José Juan (Auditio, 2021)
This article is the first in a series of studies aimed at describing the characteristics of the Auditory-Evoked Brainstem Responses of the (ABR) in both normal hearing and hard of hearing subjects. In interpreting these electrophysiological recordings, it is necessary to know the normality values of the latency and amplitude of the main components and their relationship with the different intensities, as well as the values of the interwave intervals and the possible interaural differences. These normality values vary depending on multiple factors such as gender, age, stimulation and recording parameters or the conditions in which the ABR are carried out. In this first work, the latency normality values of the components of the ABR are described using the stimulation and recording parameters of our laboratory in a sample of normal hearing adult subjects.